Kodematik und ihre metaglottodidaktische Relevanz - Szczodrowski, Marian (Glottodidactica, 2017)
This article deals with glottodidactic processes, seen on a level that goes beyond purely didactic-linguistic issues, that is, a level that considers their more specialized forms and that is a domain of other academic fields. The subject of the article is metaglottodidactic information concerning processes of decoding, processing, storing, and encoding language structures while learning and acquiring them. The author refers, in particular, to select problems from the field of codematics and the theory of control in processes of coding (generating and producing) foreignlanguage information on the part of the sender, the interindividual transferring of that information, the phonetic-phonological, grapho-graphic, and semantic-grammatical decoding and processing in the receiver’s language center.